2002
DOI: 10.1539/joh.44.214
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Heart Rate Variability in Taxi Drivers on Long Duty Schedules

Abstract: Blood Pressure and Heart Rate Variability in Taxi Drivers on Long Duty Schedules: Fumio KObayashi, et al. Department of Health and Psychosocial Medicine, Aichi Medical University School of Medicine Objective To clarify the mechanisms of excessive risk of cardiovascular disease among taxi drivers, the effects of taxi driving with long work hours on taxi drivers' blood pressure and heart rate variability were examined. Methods We measured the physical activity level, ambulatory blood pressure, and Holter ECG in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…These data suggest that smoking at night has a more potent acute effect on the cardiac modulation of taxi drivers than during the day. Previous studies have confirmed the presence of a circadian rhythm with the prevalence of sympathetic activity during the day and a marked increase in parasympathetic activity during the night (14,(33)(34)(35). At night, smoking taxi drivers are therefore assumed to have their own circadian rhythms, which originally decrease sympathetic activities and increase parasympathetic ones, disturbed by the effects of smoking.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These data suggest that smoking at night has a more potent acute effect on the cardiac modulation of taxi drivers than during the day. Previous studies have confirmed the presence of a circadian rhythm with the prevalence of sympathetic activity during the day and a marked increase in parasympathetic activity during the night (14,(33)(34)(35). At night, smoking taxi drivers are therefore assumed to have their own circadian rhythms, which originally decrease sympathetic activities and increase parasympathetic ones, disturbed by the effects of smoking.…”
Section: Discussionmentioning
confidence: 92%
“…Nevertheless, the mechanisms underlying the increased risk of cardiovascular disease among taxi drivers have not yet been fully investigated. An increase in blood pressure caused by long hours of driving together with various work-related stressors (4,7,(11)(12)(13)(14)(15), such as dealing with passengers, searching for potential customers along streets and roads, waiting at taxi stands for customers, traffic jams, rain, and highway driving, may contribute substantially to the increased cardiovascular risk. Some neurophysiological mechanisms (11,(15)(16)(17), including dysfunction of the autonomic nervous system, hyperreactivity of the cardiovascular system, and disturbed circadian rhythms of the endocrine system, may also occasionally result in fatal arrhythmia or chronically accelerated coronary Kobayashi et al atherosclerosis.…”
mentioning
confidence: 99%
“…38–41 In a study of Japanese taxi drivers, blood pressure during workdays was significantly higher than during non-work days. 42 Poor diet further increases CVD risk. A survey of Chicago drivers found only 5% met recommended levels of fruit and vegetable intake.…”
Section: Introductionmentioning
confidence: 99%
“…The growing taxi driver workforce is at risk for poor health status, including increased risk for cardiovascular disease (CVD). In a study of Japanese taxi drivers, blood pressure was significantly higher during work-days than during non-work days, especially among hypertensive drivers [2]. The prevalence of myocardial infarction (MI), multi-vessel disease, and CVD risk factors were significantly higher among drivers than among age-adjusted non-drivers [3].…”
Section: Introductionmentioning
confidence: 99%